Semantic Annotation and Association of Web Documents: A Proposal for Semantic Modeling in the Context of E-Recruitment in the IT Field - Bogdan Ionescu; Iuliana Ionescu; Vasile Florescu; Andrei Tinca (Journal of Accounting and Management Information Systems (JAMIS), 2012)
The emergence of the Internet has widely opened opportunities for web applications based on the modeling of textual knowledge from electronic documents, with the aim of identifying the useful parts. This is also the case of e-recruitment applications, which aim at the optimizing and automating the processes by semantic association between CVs a job offers. Our paper considers the problem of semantic-based annotation of semi-structured documents, and proposes a semantic model for e-recruitment in the IT domain.
Keywords: M15; M51; 650; e-recruitment; ontology; semantic annotation; information system; similarity measure